Optimalisasi manajemen inovasi dan kinerja rantai pasok dalam pengembangan UMKM tekstil - Nurhidayah, Rika; Muliansyah, Dadah; Teguh Wibowo, Bimo; Alvianita, Syavilla; Reskiyah, Efri (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
Innovation management and supply chain performance in textile MSMEs in Sukamurni, Balaraja are not optimized enough. This has an impact on sales figures that have not increased in the last few periods. On that basis, and considering theoretical studies, it is necessary to optimize innovation management and supply chain performance. This activity is included in the action category, which is carried out in the community service program scheme. To help MSME actors increase turnover from time to time through innovation management and supply chain performance, the community service team held a workshop to optimize innovation management and supply chain performance. The achievement of this community service activity is to increase the ability of MSME actors. In principle, based on the comparison of pre-test and post-test scores, this activity has achieved the target expected from the beginning, namely increasing community knowledge and skills. The workshop activities in this community service were held according to plan and schedule. Likewise, the completion of tasks by participants who can produce products according to the targets set by the community service team. The workshop activities in this community service showed satisfactory results. The average post-test score (after attending the workshop) is an indication that skills and knowledge have increased significantly. This can be seen from the increase in the results of the pretest posttest workshop from 74 to 80.